The Role of Nuclear Energy in Pakistan’s Low-Carbon Future - Huma Rehman (CISS Insight Journal, 2025)
Pakistan faces significant energy challenges, including rising energy demand and excessive reliance on fossil fuels, which contribute to greenhouse gas emissions and increased climate vulnerability. To address these issues, Pakistan should shift toward a sustainable and viable low-carbon future by diversifying its energy mix through the integration of clean energy sources. Nuclear energy, with its low-carbon footprint and high energy density, offers a viable solution to meet baseload electricity demand while reducing emissions. This article discusses the theoretical framework for nuclear energy in a low-carbon future. It examines the prospects of nuclear energy in Pakistan’s energy transition by analyzing current nuclear power generation capacity, future expansion plans, and policy frameworks. The paper evaluates the economic, environmental, and security aspects of nuclear power compared to renewables such as solar and wind. Additionally, it addresses important challenges, including high capital costs, nuclear waste management, and public perception, while highlighting developments in nuclear reactor technology and exploring opportunities for international cooperation. The findings suggest that the peaceful use of nuclear energy, alongside renewables, can significantly contribute to decarbonization while enhancing energy security and promoting sustainable development. Strategic investments, regulatory reforms, and public engagement are essential to realizing this potential.